A new method of roundness error evaluation based on twin support vector machines. (5th May 2021) - Liu, Dongliang; Zheng, Peng; Cao, Manyi; Yin, Haotian; Xu, Yingjie; Zhang, Linna
Abstract: The geometric error determines the product quality and function to a certain extent. Among them, the roundness error is one of the important indicators for evaluating the geometric error of shaft parts. With the increase of industrial requirements, there are higher requirements for the accuracy and efficiency of roundness error evaluation. However, most of the traditional roundness error evaluation models used in the industry can no longer meet the needs of current industrial processing in terms of efficiency and accuracy. This paper proposes a new roundness error evaluation method based on twin support vector machines (TWSVMs). First, according to the roundness error evaluation and the TWSVMs theory, the roundness error evaluation model with the TWSVMs is obtained. Then, experimental research and analysis are carried out, and the accuracy and efficiency of the traditional roundness evaluation method and the new method are compared. The research results show that the new roundness evaluation method based on the TWSVMs proposed in this paper can efficiently and accurately evaluate the roundness error, and can be applied to the online evaluation of the roundness error in industrial processing to improve the processing efficiency.